2020
DOI: 10.21873/cgp.20182
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Anionic-phosphate-platinum Complex Effectively Targets a Cisplatinum-resistant Osteosarcoma in a Patient-derived Orthotopic Xenograft Mouse Model

Abstract: Background/Aim: We have previously developed a novel bone-targeting platinum compound, 3Pt, and showed that it has strong inhibitory activity against osteosarcoma cells and orthotopic cell-line xenograft mouse models. In the present report, we compared the efficacy of 3Pt to cisplatinum (CDDP) in a CDDP-resistant relapsed osteosarcoma patient-derived orthotopic xenograft (PDOX) mouse model. Patients and Methods: The tumor of a patient with osteosarcoma of the distal femur was treated with CDDP-based chemothera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
1
5
1
Order By: Relevance
“…As such, it can be used as a novel reference model by other researchers in establishing other mouse tumor models. This contradicts the findings reported in other articles using orthotopic xenotransplantation of human osteosarcoma cell lines (Igarashi et al, 2020). There are numerous techniques for constructing a mouse tumor model.…”
Section: Discussioncontrasting
confidence: 75%
“…As such, it can be used as a novel reference model by other researchers in establishing other mouse tumor models. This contradicts the findings reported in other articles using orthotopic xenotransplantation of human osteosarcoma cell lines (Igarashi et al, 2020). There are numerous techniques for constructing a mouse tumor model.…”
Section: Discussioncontrasting
confidence: 75%
“…These fresh tumor samples were previously transported to the laboratory on ice and established in nude mice using small tumor fragments transplanted subcutaneously (10,11,(17)(18)(19).…”
Section: Methodsmentioning
confidence: 99%
“…We developed patient-derived orthotopic xenograft (PDOX) models of all major types of malignancies, including osteosarcoma, with the technique of surgical orthotopic implantation (SOI), allowing effective and ineffective drugs to be distinguished (9)(10)(11)(12)(13). The PDOX models recapitulate human-tumor behavior better than other in vivo models due to their intact histology and correct organ-tumor microenvironment of the orthotopicallyimplanted tumor (14)(15)(16).…”
mentioning
confidence: 99%
“…Efficacy of a novel anioninc-phosphate-platinum complex on osteosarcoma PDOX. An anioninc-platinum complex, which contains 3Pt and bisphosphonates, can have high-bone and low-kidney accumulation, leading to increased anti-tumor efficacy on bone tumors and decreased nephrotoxicity compared to CDDP (39). We demonstrated that 3Pt inhibited tumor growth more effectively than CDDP in the pelvicosteosarcoma PDOX model from patient #1 (39).…”
Section: Identification Of Effective Experimental Drugs For Osteosarcoma With the Pdox Modelmentioning
confidence: 77%